2019
DOI: 10.1371/journal.pone.0217523
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of circulating miRNAs in systemic lupus erythematosus

Abstract: BackgroundIn recent years, many studies focused on the association between the microRNAs (miR-NAs) and the risk of systemic lupus erythematosus (SLE), especially miRNA-21 (miR-21). We aimed to investigate the role of circulating miRNAs, especially the miR-21, as a biomarker in detecting SLE. MethodsWe searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and China National Knowledge Infrastructure through Mar 3th, 2019. We performed this metaanalysis in a fixed/random-effect model using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…Further, we showed that protein level of IL-12 and IL-21 are positively correlated with miR21, miR25, miR186 expression levels. Our data for miR21 agreed with other investigators who have found similar increased expression level in SLE patients ( 13 , 58 , 63 69 ). Previously it was shown that miR21 contributes to DNA hypo-methylation in lupus CD4 + T cells by targeting DNA methyltransferase 1 ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…Further, we showed that protein level of IL-12 and IL-21 are positively correlated with miR21, miR25, miR186 expression levels. Our data for miR21 agreed with other investigators who have found similar increased expression level in SLE patients ( 13 , 58 , 63 69 ). Previously it was shown that miR21 contributes to DNA hypo-methylation in lupus CD4 + T cells by targeting DNA methyltransferase 1 ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…Since miRNA are post-transcriptional regulators of gene expression, mediated via suppression of the translation of mRNAs or degradation of target mRNAs, they transmit executable instructions. They have been identified as potential biomarkers in many fields including cancer [ 25 ], AD [ 26 ], systemic lupus erythematosus [ 27 ], traumatic brain injury [ 28 ], cardiovascular disease [ 29 ], PD [ 30 ], multiple sclerosis [ 31 ] and diabetes [ 32 ]. Since miRNA are found as cargo within EVs and the lipid membrane surrounding EVs protects the miRNA from enzymatic degradation, there is good rationale for examining miRNA extracted from isolated EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Another and negatively correlated with IL-2 levels. 44,45 One study also found that miR-21 was elevated in the peripheral blood mononuclear cells in lupus patients, 46 and expression of miR-155 could be a potential biomarker of SLE diagnosis and disease activity prediction. 47 For treatment, there were some attempts to use microRNA as a means of therapeutic targeting for SLE.…”
Section: Discussionmentioning
confidence: 97%
“…Another study tested the levels of miR‐31, miR‐21, and IL‐2 concentrations in the plasma of SLE patients. They found that miR‐21 was upregulated and negatively correlated with IL‐2 levels 44,45 . One study also found that miR‐21 was elevated in the peripheral blood mononuclear cells in lupus patients, 46 and expression of miR‐155 could be a potential biomarker of SLE diagnosis and disease activity prediction 47 …”
Section: Discussionmentioning
confidence: 98%